2003
DOI: 10.1152/ajpendo.00110.2003
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of adiponectin by adipose tissue-derived cytokines: in vivo and in vitro investigations in humans

Abstract: Adiponectin is an adipose tissue-specific protein that is abundantly present in the circulation and suggested to be involved in insulin sensitivity and development of atherosclerosis. Because cytokines are suggested to regulate adiponectin, the aim of the present study was to investigate the interaction between adiponectin and three adipose tissue-derived cytokines (IL-6, IL-8, and TNF-alpha). The study was divided into three substudies as follows: 1) plasma adiponectin and mRNA levels in adipose tissue biopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
445
2
21

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 665 publications
(509 citation statements)
references
References 43 publications
41
445
2
21
Order By: Relevance
“…The molecular mechanisms involved in adiponectin secretion and multimerization as well as their regulation have not been deciphered. 10 However, it is clear that reactive oxygen species 29 and pro-inflammatory cytokines 30 are potent inhibitors of adiponectin gene expression. As BJ has a very high anti-oxidant activity, more than four times greater than NJ, 18,31 it could reduce oxidative stress in obese diabetic mice.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms involved in adiponectin secretion and multimerization as well as their regulation have not been deciphered. 10 However, it is clear that reactive oxygen species 29 and pro-inflammatory cytokines 30 are potent inhibitors of adiponectin gene expression. As BJ has a very high anti-oxidant activity, more than four times greater than NJ, 18,31 it could reduce oxidative stress in obese diabetic mice.…”
Section: Discussionmentioning
confidence: 99%
“…8,19 Several in vitro studies have clearly demonstrated that, cytokines such as IL-6, IL-8, IL-1b and TNF-a are potent inhibitors of adiponectin. 20,28,33 Recently, it was shown that weight reduction in obese subjects leads to a marked decrease in proinflammatory proteins. 5 These proteins, adipose tissue and insulin resistance, seem to be partly involved in the process causing chronic subclinical inflammation, associated with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…19 In vitro incubation of human adipose tissue with IL-6 resulted in a decrement in adiponectin mRNA levels, suggesting that cytokines may inhibit adiponectin and so playing an important role in the association between adiponectin and insulin resistance. 20 However, none of these studies provided data of adiponectin comparing patients with different stages of glucose tolerance. Therefore, we investigated the cross-sectional and longitudinal association of adiponectin plasma levels with CRP and IL-6 in morbidly obese women with normal (NGT) and impaired glucose tolerance (IGT) as well as T2D before and after gastroplastic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Adiponectin is an anti-inflammatory adipokine that has an insulin-like role in promoting vasodilatation and anti-atherosclerotic effects, stimulating nitric oxide production in endothelial cells and inhibiting the release of proinflammatory adipokines, which in turn contribute to a coupling of vascular insulin resistance and endothelial dysfunction. 8,9 Moreover, a decrease in insulin sensitivity is related to increases in the endothelial expression of plasminogen activator inhibitor type-1 (PAI-1) and cellular/vascular adhesion molecules implicated in the initiation of endothelial dysfunction. 4,9,10 The prevalence of cardiovascular diseases in children and adolescents is increasing, and there is evidence that carotid IMT is higher in children with diabetes, hypercholesterolemia and obesity than in healthy controls.…”
Section: Introductionmentioning
confidence: 99%